Suffering, Self-Acceptance and Finding the Meaning of Life in Women with Breast Cancer After Mastectomy - Igriya Fauzi Nabilah; Triantoro Safaria; Siti Urbayatun (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
Breast cancer is a malignant disease that most often occurs in women and provides a major change in their lives. Suffering, self-acceptance and finding the meaning of life are the main searches and objectives of this research. The aim is to describe the process of deep meaning in life that is felt by women with breast cancer after mastectomy. This study uses a qualitative study with a phenomenological approach. Researchers get data by means of purposive sampling technique, interviews, and the willingness of the subject to be interviewed. The sample is 6 women with breast cancer. The findings in this study indicate that in the process of finding the meaning of life, the subject goes through several phases of life. The first phase is the suffering phase, the second phase is the self-acceptance phase. the third phase is the phase of finding the meaning of life, and the fourth phase is the phase of meaningful life. Women realize the importance of maintaining a healthy body and make big changes in their lives. Women take curative actions to reduce their suffering, then accept the reality and analyze how much wisdom they get after mastectomy. Breast cancer survivors realize their lives are more meaningful, think positively, accept their shortcomings, are more religious and are optimistic about their future. Kanker payudara merupakan penyakit ganas yang paling banyak terjadi pada wanita dan memberikan perubahan besar dalam hidupnya. Penderitaan, penerimaan diri dan penemuan makna hidup menjadi penelusuran dan tujuan utama dalam penelitian ini. Tujuannya adalah untuk mendeskripsikan proses pemaknaan hidup mendalam yang dirasakan wanita pengidap kanker payudara pasca mastektomi. Studi ini menggunakan studi kualitatif dengan pendekatan fenomenologis. Peneliti mendapatkan data dengan cara teknik purposive sampling, wawancara, dan kesediaan subjek untuk diwawancarai. Sampelnya adalah wanita pengidap kanker payudara sebanyak 6 orang. Temuan pada hasil penelitian ini menunjukan bahwa dalam proses menemukan makna hidup, subyek melalui beberapa fase kehidupan. Fase pertama adalah fase penderitaan, fase dua adalah fase penerimaan diri, fase ketiga adalah fase penemuan makna hidup, dan fase empat adalah fase kehidupan bermakna. Wanita menyadari pentingnya menjaga kesehatan tubuh dan membuat perubahan besar dalam hidupnya. Wanita melakukan tindakan kuratif untuk mengurangi penderitaannya, lalu menerima kenyataan yang ada dan menganalisa seberapa banyak hikmah yang ia dapatkan setelah mastektomi. Para penyintas kanker payudara menyadari hidupnya lebih bermakna, berpikir positif, menerima kekurangannya, lebih religius dan optimis akan masa depannya.